1, 2, 3‐Diazaborinine: A BN Analogue of Pyridine Obtained by Ring Expansion of a Borole with an Organic Azide. Issue 1 (30th November 2018) - Lindl, Felix; Lin, Shujuan; Krummenacher, Ivo; Lenczyk, Carsten; Stoy, Andreas; Müller, Marcel; Lin, Zhenyang; Braunschweig, Holger
Abstract: A new pathway for the ring expansion reaction of antiaromatic boroles with organic azides is reported. While the reaction usually leads to 1, 2‐azaborinines, it was diverted to the formation of a 1, 2, 3‐diazaborinine by changing the electronic characteristics of the reagents. The isolable azo‐azaborinine intermediate initially formed from the reaction of 1‐(2, 3, 4, 5‐tetraphenylborolyl)ferrocene with 4‐azido‐ N, N ‐dimethylaniline gradually decomposed to a 1, 2, 3‐diazaborinine and benzonitrile. Both the spectroscopic properties and the reactivity of the heteroaromatic compound show analogies to pyridine, to which it is isoelectronic. Density functional theory (DFT) calculations provided insight into the mechanism of this unusual transformation. Abstract : Nitrile & error : A new pathway for the ring expansion reaction of boroles with organic azides is presented, leading to a 1, 2, 3‐diazaborinine instead of the expected 1, 2‐azaborinine. Mechanistic DFT calculations provided insight into the mechanism of formation of the BN2 C3 heterocycle, and spectroscopic and reactivity studies demonstrated the analogies of the 1, 2, 3‐diazaborinine to pyridine.